Ketamine does not rescue plaque load or gap detection in the 5XFAD mouse model of Alzheimer's disease - Alexa L. Wright; Aldis P. Weible; Olivia B. Estes; Michael Wehr (Frontiers in Aging Neuroscience)
Ketamine has received growing attention for its effects on neuroplasticity and neuroinflammation, and as a treatment for depression and other mental health disorders. Recent evidence suggests that early sensory and behavioral deficits in Alzheimer's disease could be caused by synaptic disruption that occurs before irreversible neuropathology. This raises the possibility that ketamine could slow down or prevent network disruption and the ensuing sensory and behavioral deficits in Alzheimer's. Here we tested this idea in the 5XFAD mouse model of Alzheimer's, using either an acute single injection of ketamine, or chronic daily injections over 15 weeks. We tested the effects of ketamine on both amyloid plaque load and on a behavioral auditory gap detection task that is an early Alzheimer's biomarker in both mice and humans. We found that ketamine had no effect on plaque load, nor any effect on gap detection, for either acute or chronic dosing. Chronic ketamine facilitated startle responses specifically in 5XFAD mice, but this could simply be related to experience-dependent effects on stress or habituation rather than any rescue effect of ketamine on Alzheimer's-related deficits. We did find robust correlations between gap detection deficits and plaque load in auditory cortex and in the caudal pontine reticular nucleus, demonstrating that the behavioral deficits seen in 5XFAD mice are directly related to amyloid accumulation in these brain regions, and confirming the validity of gap detection as an early biomarker of Alzheimer's. Ketamine, however, had no effect on the strength of these correlations. We conclude that ketamine has no beneficial effect on the development of behavioral gap detection deficits or plaque load in the 5XFAD Alzheimer's mouse model, following either an acute single dose or a chronic daily dose regimen.